21st century American environmental ideologies: a re-evaluation. Issue 1 (2nd January 2018) - Hultgren, John
Abstract: Around the turn of the century, myriad books and articles – from academics, journalists, organizational leaders and grassroots activists – explored the state of American environmentalism, outlining ideological antagonisms and tracing the contours of possible twenty-first century trajectories. In recent years, however, there have been few such analyses, and those that do exist continue to rely on the ideal types of the past. This article explores the shifting ideological contours of American environmentalism by (1) detailing how extant works categorize American environmental ideologies, and (2) employing discourse and content analysis of sixteen American environmental organizations to consider whether existing ideal-types capture the ideological variability driving contemporary environmental practice. It concludes by outlining six twenty-first century American environmental ideal-types: wilderness preservationism; liberal environmentalism; traditional environmental justice; techno-ecological optimism; socio-ecological progressivism; and socio-ecological radicalism. The article argues that the latter three ideological variants signal an ontological shift that cuts to the core of environmental practice.